MANAGING TRANSITIONAL CHANGE: STAFF PERSPECTIVES FROM TECHNICAL UNIVERSITIES IN GHANA - Essel, Jonathan (International Online Journal of Education and Teaching, 2025)
The study focuses on examining the perspective of staff on organisational transition change of Technical Universities in Ghana. It employed case study research design. The study sampled participants purposeful and acknowledged the necessity of ethics in the investigative process. The Seven Drivers of Change model was employed as a theoretical framework to interrogate the issues at hand. The study found that the perspective of staff on the conversion of polytechnics into technical universities or organisational transition change was influenced by some organisational politics, which influenced some biases on staff to fully accept the change. The study also revealed that employee mistrust and lack of confidence influenced organisational transitional transformation. The impact on institutional identity and culture and academic heterogeneity were all revealed to influence organisational transition change. The study concluded that policymakers should examine and include stakeholder input as well as comprehensive consensus building when implementing organisational management and change procedures.